Composition in the beginning band classroom: using one to one technology - Frein, Angelete Dawn (Kansas State University, 2022)
The lessons demonstrated in this report introduce composition into the beginning band classroom with a one-to-one technology setting. The purpose of this project is to incorporate the creating standard into my classroom on a consistent basis with students. For the instrumental music classrooms, we follow the 2014 Music Standards of performing, responding, creating, and connecting. The performing and responding standards tend to be at the forefront in the instrumental classroom setting. However, all musicians should be allowed to develop their creating skills while they are developing their performance and responding skills. The students used for this project are sixth graders, in their first year of playing a wind or percussion instrument. The classes are split into two sections, woodwinds/percussion and then brass the opposite day. Each student had access to a Chromebook and all assignments were posted digitally using Google Classroom. All of my students that I teach were a part of this composition project and throughout the teaching video, you will see different classes. The composition project was broken down into five extended lessons. The lesson plans extend over multiple days due to the frequency that I see students. Lesson plan one reviewed music symbols and terminology through prior knowledge. Lesson plan two focused on rhythm and had the students compose their own rhythm. Lesson plan three focused on melody which incorporated new material relating key signatures. The students wrote their own melody at the end of this unit and performed the melody for lesson plan four. The last lesson plan has the students reflect on the composition project. This data collected will allow me to gauge the effectiveness of the lessons for future use with students. I will be looking at items such as interest, knowledge gained during the lessons, and do the lessons need to be modified. My time at Kansas State University has provided an opportunity to dive deeper into concepts we briefly discussed in undergraduate courses. During this time, I have been able to strengthen my knowledge of rehearsal strategies, program organization, and leadership development to better incorporate all four music standards into the instrumental music classroom. Most importantly, I have had time to reflect on my own teaching. I focused on questioning methods I use on a daily basis and the students that we see in today’s classroom. Today’s classroom, education, and students have adapted to the use of technology due to the pandemic. Throughout this pandemic, we have engaged students in a new way. Personally, I enjoy having technology in the instrumental classroom to reinforce concepts and help develop the individual musician. Developing the individual musician allows us to raise the overall level of the ensembles we provide for students. We must have the mindset of continual growth as educators.
Keywords: Chromebooks